Optical Properties of Pure and Eu Doped ZnSe Films Deposited by CSVS Technique - M.M. Ivashchenko; A.S. Opanasyuk; I.P. Buryk; V.A. Lutsenko; A.V. Shevchenko (Журнал нано- та електронної фізики)
Pure (ZnSe) and europium doped (ZnSe:Eu) zinc selenide films were evaporated onto glass substrates using the close-spaced vacuum sublimation (CSVS) technique at different deposition conditions (substrate temperature). The fundamental optical parameters such as optical density, extinction coefficient, refraction index, real and imaginary parts of optical dielectric constant, band gap were evaluated in transparent region of transmittance and absorbance spectrum. Optical spectroscopy analysis shown that in both cases deposited films had a high level of transmittance values (55-65 % for ZnSe films and 80-90 % for ZnSe:Eu films). Moreover, evaluated values of the films optical band gap were in the range of Eg  (2.63-2.69) eV for ZnSe films and Eg  (2.77-2.81) eV for ZnSe:Eu for films with increasing of the films substrate temperature. Fourier-transformed infra-red (FTIR) analysis of deposited ZnSe and ZnSe:Eu films shown that all investigated samples are well-crystalline and identified vibrations are typical for II-VI semiconductors.